Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Support-Seekers’ Community Knowledge on Their Expressed Satisfaction with the Received Comments in Mental Health Communities

Abstract: Online mental health communities (OMHCs) are prominent resources for improving people's mental wellbeing. An immediate cue of such improvement is support-seekers' satisfaction expressed in their replies to the received comments. However, the comments that seekers find satisfying may change with their community knowledge, e.g., measured by tenure and posting experience in that community. In this paper, we first model the amount of satisfaction conveyed in the support-seekers' replies to the received comments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
(165 reference statements)
0
11
0
Order By: Relevance
“…One of the main forms of communication among members in an OMHC is that help-seekers initiate posts (help-seeking posts) and supporters reply (reply posts). Through these types of posts, members can provide each other with emotional, informational, and other forms of support (Peng et al, 2021). Psychological support-seekers judge the responses of social supporters through information disclosure, information quality, and perceived credibility of information source; they perceive usefulness from the responses, and thus decide whether to engage in further self-disclosure and/or deep interaction (support-seekers respond to the reply posts, i.e., re-posts), as shown in Figure 1.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…One of the main forms of communication among members in an OMHC is that help-seekers initiate posts (help-seeking posts) and supporters reply (reply posts). Through these types of posts, members can provide each other with emotional, informational, and other forms of support (Peng et al, 2021). Psychological support-seekers judge the responses of social supporters through information disclosure, information quality, and perceived credibility of information source; they perceive usefulness from the responses, and thus decide whether to engage in further self-disclosure and/or deep interaction (support-seekers respond to the reply posts, i.e., re-posts), as shown in Figure 1.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Online mental health communities (OMHCs) are the prevalent medium of exchanging social support with peers experiencing similar challenges, providing high accessibility and anonymity [21,24,25,28,38]. To date, several studies have explored the dynamics of peer supports in OMHCs or mental health-related discussions, such as relationship between user satisfaction and their community knowledge [28], cross-cultural variances of OMHCs [26], and motivations and practices of mental health discussions in Twitch [40].…”
Section: Related Work 21 Online Mental Health Communitymentioning
confidence: 99%
“…Specifically, previous works suggested that people were more satisfied when their received support matches the needed support [41,42], in the form of informational or emotional support. These are known to increase both members' commitment and satisfaction when they sought and received the matched support [28,44]. Here, emotional supports are particularly known to lead support-seeker to express more satisfaction when receiving emotional support from the reaction [28].…”
Section: Related Work 21 Online Mental Health Communitymentioning
confidence: 99%
See 2 more Smart Citations